2021
DOI: 10.1007/s11356-021-14817-2
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 pandemic disrupt sustainable supply chain process? Covering some new global facts

Abstract: The adverse effects of the coronavirus 2019 (COVID-19) pandemic are widely visible in the economic structure, while the principal causal factor is the disruption of the supply chain process that leads to the economies into a global depression. The purpose of the study is to identify the critical factors that affect the global sustainable supply chain process in the cross-sectional panel of 38 European countries, 14 North American countries, 40 Asian countries, and a heterogeneous panel of 111 countries. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The study also identified the remedial measures to deal with disruption in SC from COVID-19. Anser et al ( 2021 ) analysed the critical factors that affect the sustainable SC in COVID-19. Karuppiah et al ( 2021 ) analysed the challenges of COVID-19 in the humanitarian SC using the analytical hierarchy process (AHP).…”
Section: Knowledge-based Supply Chain: Emerging Themesmentioning
confidence: 99%
“…The study also identified the remedial measures to deal with disruption in SC from COVID-19. Anser et al ( 2021 ) analysed the critical factors that affect the sustainable SC in COVID-19. Karuppiah et al ( 2021 ) analysed the challenges of COVID-19 in the humanitarian SC using the analytical hierarchy process (AHP).…”
Section: Knowledge-based Supply Chain: Emerging Themesmentioning
confidence: 99%
“…The COVID-19 pandemic has also affected, both positively and negatively, the adoption of innovation in the logistics sector. On the one hand, authors have argued that the COVID-19 pandemic sped up the transformation and innovation in the logistics sector, e.g., [8][9][10][11]. Online businesses blossom since the start of the pandemic and lead to increased need for innovations in logistics to deliver goods to consumers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Online businesses blossom since the start of the pandemic and lead to increased need for innovations in logistics to deliver goods to consumers [8]. Companies have also recognized the need to adopt robust and resilient supply chains and logistics by making them smart, digitalized, and sustainable during the COVID-19 pandemic [9,10]. For example, in airline industries, COVID-19 led to innovations such as the utilization of touchless technologies at airports, the use of ultraviolet light (UV) for disinfecting aircrafts, and the use of biometrics to accelerate check-in processes [11].…”
Section: Introductionmentioning
confidence: 99%
“…1 supports these statistics to show that the weekly Shanghai containerized freight index in main service routes reached the maximum level during the worst of the COVID-19 pandemic, compared to past years. This fact implies that supply chain disruption caused a significant increase in freight rates and led to an adverse impact on a sustainable supply chain across the globe (Anser et al, 2021 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%